2023
DOI: 10.1002/casp.2727
|View full text |Cite
|
Sign up to set email alerts
|

A social identity approach to mental health help‐seeking behaviour in prisoners: A systematic review

Abstract: Prevalence of mental health difficulties is demonstrably higher in prison rather than general populations. Compounding this, prisoners often display a reluctance to seek help, which can undermine rehabilitation. Recent years has seen an increase in studies exploring the factors involved in help‐seeking behaviours amongst prisoners. However, many of these studies come from different disciplines and do not use an overarching theoretical approach. Consequently, policymakers face a difficult task of synthesising a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…While Lashkay et al's (2023) study of survivors of Adverse Childhood Experiences and Lyu's (2024) survey of Lesbian, Gay and Bisexual (LGB) group members in China attest to the impacts of the beliefs and actions of outgroups on the identity processes occurring within groups, a number of papers attest to effects in the other direction. For example, Byrne, Bradshaw, Kerin, and Pepe's (2023) theoretically framed metareview of prisoners' experiences indicates how maintaining a positive prisoner identity in front of other inmates could have an inhibitory effect on accessing intergroup help from prison staff. Conversely, Riikonen, Finell, Seppälä, and Stevenson's (2023) survey work with Finnish and immigrant mothers in Helsinki neighbourhoods showed that identifying with other local mothers positively predicted social support, which in turn positively predicted participants' ability to cope with the challenges of intergroup contact.…”
Section: The Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…While Lashkay et al's (2023) study of survivors of Adverse Childhood Experiences and Lyu's (2024) survey of Lesbian, Gay and Bisexual (LGB) group members in China attest to the impacts of the beliefs and actions of outgroups on the identity processes occurring within groups, a number of papers attest to effects in the other direction. For example, Byrne, Bradshaw, Kerin, and Pepe's (2023) theoretically framed metareview of prisoners' experiences indicates how maintaining a positive prisoner identity in front of other inmates could have an inhibitory effect on accessing intergroup help from prison staff. Conversely, Riikonen, Finell, Seppälä, and Stevenson's (2023) survey work with Finnish and immigrant mothers in Helsinki neighbourhoods showed that identifying with other local mothers positively predicted social support, which in turn positively predicted participants' ability to cope with the challenges of intergroup contact.…”
Section: The Special Issuementioning
confidence: 99%
“…As mentioned previously, the methodological diversity of the work allows a greater consideration of how generic group processes operate within specific circumstances, and this is brought out very clearly in those studies of groups in organisational contexts. As noted above, Byrne et al's (2023) theoretically guided metareview highlights how the structure and organisation of prison life serves to inhibit help‐seeking for mental health problems, while Wakefield et al's (2024) study of veterans' experiences notes how the ethos and policies of the military can inhibit or even undermine the efforts of retiring service personnel to socially reintegrate. Likewise, both Harkin et al (2023) and Gray et al's (2023) papers on the effects of COVID‐19 on local communities point to the importance of the local community infrastructure in facilitating or inhibiting active involvement, while Filippi, Peters, and Suitner's (2023) paper documents the relationships between organisational decision‐making ethos and the well‐being of employees in the United States, United Kingdom and Italy.…”
Section: The Special Issuementioning
confidence: 99%